(3GdJMaIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3dh WQb ddYGbd Edi UQa GdeYQha Yf GdeYGQa NUhUkG EPG cGf GdeYQha CaVd YUeI JJeKd HgG cd ef SYO HGdMjGI s
(3BNQgG (B:s
(3hJJQc GdCZJQGQ HRNGQa gPg GdOGQ hJbHd Ydi cSH NjQGJ GdOGQ GdCdgi Cbhd bhdi gPG JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdMOjK h GdeUWdMs